Significance of parathyroid scintigraphy and correlation of findings with parathyroid hormone values in patients undergoing hemodialysis - Nermana Ahmetbegović; Nadira Suljagić; Vahidin Katica (Medicinski glasnik, 2017)
Aim: To compare finding of thyroid gland scintigraphy with serum concentration of parathyroid hormone in patients undergoing hemodialysis. Methods: This retrospective-prospective study included 50 patients undergoing hemodialysis with established hyperparathyroidism who were treated at Cantonal Hospital Zenica in the period 2009-2014. Besides anthropological data, concentration of parathyroid hormone in serum of patients was monitored too. Scintigraphy was performed at the Department of Nuclear Medicine using two-headed gamma camera Prism 2000xp. Results: Of the total number of 50 patients, 24 (48%) were males and 26 (52%) were females. The average age was 49.34±11.82 years. A total of 17 (34%) patients had normal findings of scintigraphy, 11 (22%) had mildly pronounced uptake of radiopharmaceuticals (score of 1), 14 (28%) had moderately pronounced uptake (score of 2), and eight (16%) had intensive uptake of radiopharmaceuticals (score of 3). A statistically significant difference was established in the length of hemodialysis treatment and scintigraphy finding (p=0.041). Conclusion: Scintigraphy of parathyroid glands in patients undergoing hemodialysis allows us to select them for parathyroidectomy. Scintigraphy of parathyroid glands and a value of parathormone in serum should be incorporated into the test algorithm for patients with secondary hyperparathyroidism caused by chronic kidney disease.
Keywords: chronic kidney disease; hyperparathyroidism; parathyroidectomy